Assistance in Making Islamic Education Learning Media at the Al-Markaz Al-Islami Darul Istiqamah Sinjai Islamic Boarding School - Suriyati,; Jamaluddin,; Mutmainnah,; Arifin, Afdal (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2025)
Learning media is used in the learning process to facilitate teachers in implementing learning, one of the media that is often used in the learning process is a wall magazine (mading). This assistance aims to enable students to know how to make learning media and to know or understand learning media in the learning process. The method used by researchers in this community service is the PAR (Participatory Action Research) method which has three stages, namely: the planning stage, the implementation stage, and the reflection stage. This community service was carried out at the Al-Markaz Al-Islami Darul Istiqama Sinjai Islamic Boarding School. The subjects in this community service were 24 students. The results obtained from the beginning to the end of the community service were that students were able to make learning media in the form of wall magazines (mading) and understood the usefulness of media in the learning process.